Light-activated multimodal nanoplatform for enhanced synergistic therapy of breast cancer - Yu Liu; Senyi Gong; Waleed Aldahmash; Kamran Ashraf; Zhanxia Li; Imran Mahmood Khan; Sobia Niazi; Meijin Guo; Ali Mohsin (Scientific Reports)
Abstract Breast cancer poses a significant health threat to women, as traditional chemotherapy often fails due to multidrug resistance and tumor adaptability. Moreover, the anti-apoptotic nature of these tumors limits the effectiveness of conventional treatments. Current therapeutic approaches, including photodynamic therapy (PDT), face limitations in clinical application due to poor water solubility of photosensitizers and challenges in targeted delivery. This study aims to develop a multifunctional nanosystem that integrates PDT with gene therapy to enhance breast cancer treatment efficacy. Firstly, Fe3O4 hollow nanospheres were prepared to carry Ce6 drug to kill breast cancer cells via chemodynamic therapy and PDT, respectively. To overcome the drawback of poor water solubility of PDT, HA/G3139/Ce6@Fe3O4 nanosystem was synthesized, which combines the benefits of G3139 antisense oligonucleotides for gene therapy and hyaluronic acid for encapsulation and targeting CD44 receptor. The developed novel nanosystem exhibits excellent biocompatibility and pH responsiveness, significantly enhancing its cancer cell-killing capability under light exposure. When the therapeutic system enters cancer cells and decomposes in the acidic environment, it releases Ce6 and G3139. On one hand, the photosensitizer Ce6 generates cytotoxic ROS upon irradiation, killing cancer cells; on the other hand, G3139 binds to the anti-apoptotic gene BCL-2 in cancer cells, downregulating the protein and inhibiting tumor proliferation. The novel nanosystem demonstrates synergistic anti-cancer effects by combining PDT, gene therapy, and chemodynamic therapy, leading to enhanced apoptosis in breast cancer cells. In conclusion, this approach offers a promising strategy for more effective and targeted breast cancer treatment.